Strategi Pemasaran Word of Mouth dalam Membangun Reputasi dan Meningkatkan Pelanggan Toko Bangunan UD. Putri Jaya Denpasar - I Putu Mas Oktaviana Howard; Ni Ketut Arniti (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
This study aims to analyze the role of Word of Mouth (WOM) marketing strategies in building business reputation and increasing the number of customers at UD Putri Jaya Building Materials Store in Denpasar. The increasingly intense competition in the building materials retail sector requires the implementation of effective, adaptive, and low-cost marketing strategies, making WOM a strategic alternative due to its high credibility derived from real customer experiences. This research employed a descriptive qualitative method with a case study approach. Data were collected through in-depth interviews, observations, and documentation involving the business owner, employees, as well as regular and new customers. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing. The results indicate that Word of Mouth serves as the primary marketing strategy at UD Putri Jaya and is formed organically through positive customer experiences. The effectiveness of WOM is supported by the implementation of the 7P marketing mix, including product quality and completeness, competitive and reasonable pricing, strategic location and delivery services, friendly and informative employee interactions, efficient service processes, and well-maintained physical facilities. These factors contribute to customer satisfaction, trust, and a positive business reputation, which in turn encourage repeat purchases, customer loyalty, and customers’ willingness to recommend UD Putri Jaya to others. Therefore, it can be concluded that Word of Mouth is an effective marketing strategy for building reputation and increasing the number of customers at UD Putri Jaya Building Materials Store in Denpasar.